Sub 150 nm Nanoscale Gallium Based Metal–Organic Frameworks Armored Antibiotics as Super Penetrating Bombs for Eradicating Persistent Bacteria. (11th August 2022) - Huang, Kai; Wang, Jinbing; Zhang, Qinghao; Yuan, Kai; Yang, Yiqi; Li, Fupeng; Sun, Xiaojiang; Chang, Haishuang; Liang, Yakun; Zhao, Jie; Tang, Tingting; Yang, Shengbing
Abstract: Persistent bacteria, such as intracellular and biofilm bacteria, are critical challenges in clinic treatment because they are refractory to antibiotics management under the shelter of cytomembrane and biofilm. Conventional strategies to combat intracellular bacteria are using high doses of antibiotics, which may bring the risk of drug resistance, and debridement of the biofilm increases patients' pain and economic burden. Currently, the use of antibiotics is irreplaceable and it is necessary to develop new strategies to enable common antibiotics to penetrate the cytomembrane and biofilm, and then kill the bacteria. Hence, a nanoscale gallium‐based metal–organic framework (GaMOF) nanoparticles that can stride across cell membranes as antibiotics carriers, disable the biofilm via disrupting bacteria Fe metabolism, and enhance the antibiotic potency for the two intractable germs is constructed. The synthesized GaMOF exhibits a high BET surface area of up to 1299.53 m 2 g −1, uniform particle size of ≈100 nm, monodispersed spherical morphology with virus‐like surfaces, and good biosafety. The nano MOF structure and Ga intrinsic inhibiting bacteria activity armored antibiotics as "super‐penetrating bombs" to eradicate the two types of elusive bacteria. Moreover, intracellular bacteria‐induced pyroptosis and associated inflammation in vivo are alleviated by GaMOF and cured by GaMOF united with antibiotics treatment. Abstract : In this study, nanoscale gallium‐based metal–organic framework (GaMOF) nanoparticles that can stride across cell membranes as antibiotics carriers and disable the biofilm via disrupting Fe metabolism, are constructed to enhance the antibiotic potency for persistent bacteria, including intracellular and biofilm bacteria. Furthermore, intracellular bacteria‐induced pyroptosis is alleviated by GaMOF and cured by GaMOF in combination with antibiotics treatment.